2010
DOI: 10.2478/v10182-010-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-B Radiation on Antioxidative Enzyme Activity in Cucumber Cotyledons

Abstract: Ultraviolet-B (UV-B) radiation negatively affects plant cells, causing reactive oxygen species (ROS) to be generated. To study the effects of increased UV-B exposure on antioxidant processes, we exposed germination-stage cucumber seedlings to increased ultraviolet radiation and analyzed hydrogen peroxide content and the activity of superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPX) and syringaldazine peroxidase (SPX). Enzymatic antioxidant system activity generally increased after UV-B suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Reduced photosynthesis, decreased protein synthesis and production of ROS species are among them [39][40][41][42][43][44]. However, there are other types of abiotic and biotic stresses that can also produce ROS, such as singlet oxygen, hydrogen peroxide, and hydroxyl radicals, in plants [41][42][43][44]. Plants have developed several defense systems against ROS-induced harmful effects.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced photosynthesis, decreased protein synthesis and production of ROS species are among them [39][40][41][42][43][44]. However, there are other types of abiotic and biotic stresses that can also produce ROS, such as singlet oxygen, hydrogen peroxide, and hydroxyl radicals, in plants [41][42][43][44]. Plants have developed several defense systems against ROS-induced harmful effects.…”
Section: Resultsmentioning
confidence: 99%
“…Light stimulates lignin biosynthesis by inducing the polymerization of coniferyl‐alcohol, which reacts with short‐wavelength UV light into a polymer‐like lignin . Lignin biosynthesis is also activated by some peroxidase/laccase enzymes, which respond to the reactive oxygen species generated by UV light exposure . Nutrient availability, such as a Fe deficiency condition, increases the root lignification via reactive oxygen species induction .…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet-B (UV-B) radiation negatively affects plant cells, causing generation of ROS such as superoxide anions (O 2 -), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH) and singlet oxygen (O 2 ) (Beckmann et al, 2012;Lizana et al, 2009;Rybus-Zaj¹c and Kubioe, 2010;Zancan et al, 2008). Fang et al (2011), Li et al (2007 and have reported that Si increases plant tolerance to UV-B radiation.…”
Section: Uv Radiationmentioning
confidence: 99%